A Novel Copper(II) Indenoisoquinoline Complex Inhibits Topoisomerase I, Induces G2 Phase Arrest, and Autophagy in Three Adenocarcinomas - Molinaro, Caroline; Wambang, Nathalie; Bousquet, Till; Vercoutter-Edouart, Anne-Sophie; Pélinski, Lydie; Cailliau, Katia; Martoriati, Alain (Frontiers in Oncology, 2022)
Topoisomerases, targets of inhibitors used in chemotherapy, induce DNA breaks accumulation leading to cancer cell death. A newly synthesized copper(II) indenoisoquinoline complex WN197 exhibits a cytotoxic effect below 0.5 µM, on MDA-MB-231, HeLa, and HT-29 cells. At low doses, WN197 inhibits topoisomerase I. At higher doses, it inhibits topoisomerase IIα and IIβ, displays DNA intercalation properties. DNA damage is detected by the presence of γH2AX. The activation of the DNA Damage Response (DDR) occurs through the phosphorylation of ATM/ATR, Chk1/2 kinases, and the increase of p21, a p53 target. WN197 induces a G2 phase arrest characterized by the unphosphorylated form of histone H3, the accumulation of phosphorylated Cdk1, and an association of Cdc25C with 14.3.3. Cancer cells die by autophagy with Beclin-1 accumulation, LC3-II formation, p62 degradation, and RAPTOR phosphorylation in the mTOR complex. Finally, WN197 by inhibiting topoisomerase I at low concentration with high efficiency is a promising agent for the development of future DNA damaging chemotherapies.